Influência da Qualidade das Lâminas no Desempenho Mecânico à Flexão de Painéis Compensados de Hevea brasiliensis - Palma, Hernando Alfonso Lara [UNESP]; Escobar, Javier Farago [UNESP]; Ballarin, Adriano Wagner [UNESP]; Leonello, Elaine Cristina [UNESP] (FapUNIFESP (SciELO), 2012)
After concluding the main phase of commercial exploration of latex (about 30 years ago), rubber wood plantations can be utilized as an alternative source of wood for sawmills and other wood based products with more aggregate value; tendency already confirmed in countries of southeastern Asia. The main purpose of this research was to evaluate the influence of dynamic modulus of elasticity veneers on the mechanical performance in the bending of plywood made from Hevea brasiliensis. For this study, rubber tree veneers were sorted in three classes of dynamic modulus of elasticity: low (from 4887-7323 MPa), medium (from 8200-8948 MPa) and high (from 10979-13010 MPa). Panels were produced according to five treatments with different veneer classes and arrangements. Results showed significant effect of the treatments in the mechanical performance in the bending of panels. Panels with better mechanical performance were produced exclusively with medium and high dynamic modulus of elasticity. Panels made with low modulus of elasticity veneers presented lower mechanical performance even when combined with high modulus of elasticity veneers.
Influence of Veneer Quality on the Mechanical Performance in the Bending of Plywood Made from Hevea brasiliensis
Keywords: Classification; Dynamic modulus of elasticity; Rubber wood; Static bending; Hevea brasiliensis